Predictors of severe postoperative pain after orthopedic surgery in the immediate postoperative period. (November 2021) - Khalil, Heba; Shajrawi, Abedalmajeed; Henker, Richard
Abstract: Aim: Severe pain in the immediate postoperative period can negatively affect patients' quality of recovery, prolong hospital stay, and increase the risk of developing persistent pain. This study aimed to examine the predictors of severe postoperative pain in the immediate postoperative period among orthopedic trauma patients. Methods: A prospective observational study design was used. Data were collected from 153 patients that underwent orthopedic surgery procedures. Pain scores were assessed by a numeric pain scale at 45 min in the Post Anesthesia Care Unit. Physical health status was measured by the American Society of Anesthesiologists Status Classification System, and total dose of opioids (converted to morphine equivalents) and other demographic and clinical characteristics were recorded from medical records. Results: Preoperative smoking and physical health status were statistically significant predictors of severe postoperative pain in the immediate postoperative period. The odds of severe postoperative pain for smokers were 2.42 times the odds of nonsmokers. Patients with severe systemic disease showed 4.27 times lower odds of severe pain than more healthy patients. Conclusion: Preoperative predictors of severe postoperative pain should be considered when assessing and treating orthopedic patients postoperatively to assure adequate pain relief.